The Projected Establishment of the Inquisition on the Colonial Urban Frontier of the ‘Silvery’ Region: Tucumán and the River Plate (Seventeenth-Eighteenth Centuries) - Vassallo, Jaqueline (2019)
In this work we address proposals for the creation of Inquisition courts by inquisitorial, royal, and ecclesiastical authorities, between the 17th and 18th centuries, due to the immense territorial extension of the Lima court’s jurisdiction, and the problems that derived from it. This study specially focuses on the governorates of Tucumán and Rio de la Plata, as part of the so-called «región platina», a space linking population centers of the colonial urban borderland shared by Portuguese, Castilians, Spanish Creoles, and Portuguese Americans.